Population Dynamics of Thrips tabaci Lindeman (Thysanoptera: Thripidae) on Table Grapes - Schwartz, A. (South African Journal of Enology and Viticulture, 2017)
Young vegetative shoots of three table grape cultivars were infested by adults of Thrips tabaci during spring. The infestation on clusters of flowers and young fruit, which followed was brief. Maximum numbers of T. tabaci were recorded during the blossom stage. Shoots and leaves were infested by T. tabaci for the duration of the season. Several natural enemies occurred with the T. tabaci populations on the shoots and leaves of which Amblyseius addoensis Van der Merwe & Ryke, a predaceous mite, was the most numerous.